Scope and practices of sustainable procurement in Local Government Engineering Department (LGED), Bangladesh: A case study on Rupganj Upazila, Narayanganj - Sharmin, Surayia (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2022.